PENGARUH KOMPETENSI DAN KARAKTERISTIK INDIVIDU TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KOMITMEN ORGANISASIONAL ( Studi pada Badan Kepegawaian Daerah Kabupaten Rembang ) - Solikin, 1142020030 (Students Journal of Economic and Management, 2013)
The purpose of this study is to analyze the effects of competency and individual characteristics on the job performanceÂ with organizational commitment asÂ mediatorÂ in Rembang Regional Civil Service Board. The population in this study is the civil service of Rembang Regional Civil Service Board that amounts to 58 people. This studyÂ use cencuss methode for collecting data , which isÂ the whole population is taken into account. The results of this study correctly proved that modelâs ability to explain correctly , competence variableâs influence , individual characteristic and organizational commitment to job performanceÂ is amounted 53% . Whereas the otherâs is amounted 47% as explained by variables outside the data-model. Mediating effect test proved that the effects of competency and individual characteristics on the job performance are not mediated by organizational commitment . Â Kata Kunci : kompetensi, karakteristik individu, komitmen organisasional dan kinerja pegawai